'Why did you do that?' The effects of instruction on recognition and production of informal second party complaints. Issue 4 (4th July 2022) - Almalki, Ziad; Jones, Christian
ABSTRACT: There have been a number of studies on the use of complaints as a speech act. The majority of these studies have included analysis of how different first language speakers make complaints while only a limited number of studies have examined the effects of instruction on the development of complaints as a speech act. Those that have examined this area have tended to focus on oral complaints made to second parties. The current study focuses on the receptive and productive benefits of instruction in developing informal second party complaints in the context of interaction amongst peers. Using an experimental design with control and experimental groups, we examined the effects of instruction on EFL learners in Saudi Arabia as related to informal second party complaints made via WhatsApp text-chat. Results show a significant effect on receptive knowledge of complaints for the experimental group but no significant differences in terms of appropriacy of complaint production.